232k views
5 votes
5-4. Solve each of the following equations for the indicated variable. Use your Equation Mat if it is helpful. Write down each of your steps algebraically. Solve for y: 2(y − 3) = 4 Solve for x: 2x + 5y = 10 Solve for y: 6x + 3y = 4y + 11 Solve for x: 3(2x + 4) = 2 + 6x + 10 Solve for x: y = −3x + 6

1 Answer

1 vote
QUESTION 1

The given equation is :


2(y - 3) = 4
We want to solve for y. This means we have to isolate y on one side of the equation while all other constants are also on the other side of the equation,

We first divide both sides by 2 to obtain,


(2(y - 3))/(2) = (4)/(2)

We cancel out the common factors to get,


y - 3 = 2

We now group like terms to get,


y = 3 + 2

We simplify to obtain,


y = 5

QUESTION 2

The given equation is


2x + 5y = 10
We want to solve for x. This means that we need to isolate x on one side of the equation, while all other variables and constant are also on the other side of the equation.

This implies that,


2x= 10 - 5y

We now divide through by 2, to obtain,


(2x)/(2) = (10)/(2) - (5y)/(2)

This will now give us,


x = 5 - (5)/(2) y

QUESTION 3

The given equation is

6x + 3y = 4y + 11

We want to solve for y. This means that we need to isolate y on one side of the equation, while all other variables and constants are also on the other side of the equation.

We first of all group all the y terms on one side of the equation to obtain,


6x - 11 = 4y - 3y

We simplify to get,


6x - 11 = y

This implies that,


y = 6x - 11

QUESTION 4

The given equation is,


3(2x + 4) = 2 + 6x + 10

We want to solve for x. This means that we need to isolate x on one side of the equation, while all other variables and constant are also on the other side of the equation.

Let us first expand the brackets to get,


6x + 12 = 2 + 6x + 10
This implies that


6x + 12 = 6x + 12

We group like terms to get,


6x - 6x = 12 - 12

We now simplify both sides to get,


0x = 0

We don't want x to vanish, so let us try to divide both sides by zero to get,


x = (0)/(0)

This is an indeterminate form, which implies that, x has infinitely many solutions. This means that all the real numbers are solution to the equation.


\therefore \: x \in \: R

QUESTION 5

The given equation is,


y = - 3x + 6

We want to solve for x, so we add the additive inverse of 6, which is -6 to both sides of the equation to get,


y - 6 = - 3x

We rewrite this to obtain,


- 3x = y - 6

We divide through by -3 to get,


( - 3x)/( - 3) = (y)/( - 3) - (6)/( - 3)

This will give us,


x = - (y)/(3) + 2

or


x= 2 - (1)/(3) y
User Martin Strejc
by
5.8k points